Narrating alternative histories : an exploration of Jamal Mahjoub's The carrier and Amitav Ghosh's In an antique land - Eberhard, Nicole Joanne (Stellenbosch : Stellenbosch University, 2014)
Thesis (MA)-- Stellenbosch University, 2014.